Mechanical and thermal properties of cockles shell cementing material - Al-Zubaidi, Aseel Basim (Iraqi Journal of Physics, 2019)
Mortar of ordinary Portland cement was blended with cockles shell powder at different weight ratios to investigate the effect of powder admixture on their strength and thermal conductivity. Results showed that addition of cockles shell powder at 50% of mortar weight improves hardness and compressive strength notably and reduces the thermal conductivity of the end product. Results suggest the possibility to incorporate cockles shell powders as constituents in cement mortars for construction and plastering applications.